Adaptive Stilt Housing and Socio-Ecological Resilience in Coastal Settlements Under Urbanization Pressure - Asmal, Idawarni; Hayati, Arina; Suryani, Sri; Nadjmi, Nurul (Salehan Institute of Higher Education, 2025)
The water-based settlement of Cambayya, Makassar, represents a spatial adaptation by coastal communities facing urbanization, land scarcity, and dynamic marine conditions. High population density has driven the organic growth of informal stilt housing over coastal waters. This study examines spatial adaptation strategies that foster socio-ecological resilience in densely populated coastal environments. Utilizing a mixed-methods approach within a constructivist paradigm, the research combines spatial analysis, participatory observation, field surveys, interviews, and socio-ecological data interpretation. The findings reveal key adaptive responses, including the conversion of underfloor stilt areas into domestic space, the use of hybrid timber-concrete structures, and horizontal expansion into shallow waters. While adaptive, these practices exacerbate ecological degradation, such as tidal flooding, pollution, and inadequate sanitation. The study highlights the need for inclusive, sustainable spatial planning and proposes an innovative strategy: integrating stilt housing with waterfront development and cultural seascape tourism. This approach not only enhances resilience but also unlocks economic potential—estimated at over IDR 3.5 billion annually—through heritage-based ecotourism and creative industries. The study contributes a context-sensitive, community-driven spatial model for resilient coastal urbanism, positioning Cambayya as a reference for sustainable development in similar tropical coastal settlements.